Comparison of Functional Outcomes of Unilateral Periarticular Locking Plate, Hybrid Dual Plates, and Classic Dual Buttress Plates in the Treatment of Bicondylar Tibial Plateau Fractures - Chen-Yu Hung; Po-Yin Shen; Jian-Chih Chen; Yu-De Su; Tien-Ching Lee (Formosan Journal of Musculoskeletal Disorders)
Background: Bicondylar tibial plateau fractures (TPFs) present challenges in management due to articular surface involvement and soft-tissue complexities. The optimal fixation method for these fractures remains unclear. Objectives: This study aimed to compare the functional outcomes of bicondylar TPFs treated with unilateral periarticular locking plates, hybrid dual plates (locking plate and buttress plate), or classic dual buttress plates. Materials and Methods: A retrospective cohort study was conducted on 59 patients with bicondylar TPFs (Schatzker types V and VI) treated at three Level I trauma centers between 2008 and 2015. Functional outcomes were assessed using the Hospital for Special Surgery (HSS) Knee Score and the Oxford Knee Score. Results: Locking plate groups (unilateral and hybrid) demonstrated a higher percentage of excellent outcomes in HSS Knee Scores at 3 and 6 months postoperatively (p = 0.0291 and p = 0.0446, respectively) and Oxford Knee Scores at 6 months (p = 0.0253) compared to the classic dual buttress plate group. Unilateral plating showed a significantly higher percentage of excellent HSS scores at 6 months. Conclusions: The use of locking plates, either unilateral or hybrid, is associated with a higher likelihood of achieving excellent functional outcomes in bicondylar TPFs at 3 and 6 months postoperatively. Level of Evidence: Therapeutic Level III evidence, indicating a retrospective comparative study.